Leading roles : 50 questions every arts board should ask - Kaiser, Michael M., 1953- (UPCC book collections on Project MUSE., 2010)
Drawing on these and many other conversations, nationally and internationally, Kaiser's book offers members of boards and staffs the information they need to create the healthy atmosphere necessary to thriving arts organizations. Organized in a clear, readable, question and-answer format, Leading Roles covers every aspect of board participation in the life of the organization, including mission and governance; fundraising and marketing responsibilities; the relationship of the board to the artistic director, executive director, and staff; and its responsibilities for planning and budgeting. Kaiser addresses boards in crisis, international boards, and boards of arts organizations of color. Throughout, he emphasizes the importance of transparency and clarity in the board's dealings with its own members and those of the arts community of which it is a part, showing how anything less results in contentiousness that can immobilize an arts organization, or even tear it apart. --Book Jacket.